Réponses

2013-01-28T20:51:15+01:00

Bonsoir

f1(x) = -3x²-6x+2        (a+b)² =a²+b²+2ab

f2(x) = 2x²-40x+100          (a²-b²) =a²+b²-2ab 

f3(x) = -4x²+24x-37

f5(x) = x²-10x+23

f6(x) = 10x²+100x+13 

Meilleure réponse !
2013-01-28T20:56:34+01:00

F1= -3(x+1)² +5

        -3 ( x² +2x +1 )+5 = -3x² +6x -3 +5 = -3x² +6x +2

2(x -10)² =  2 (x² -20x +100) = 2x² -40x +200

3) -4 (x-3)² -1  = -4 X ( x² -6x +9) -1 = 4x² +24x -36 -1 = 4x² +24x -37

4) -( x-2)² +6

     - ( x² +4 -4x) -6

-x² -4 +4x -6 = -x² -6

(x-5)² -2

x² -10x +25 -2

x² -10x +23

 

10(x +5)² -12

10( x² +10x +25) -12

10x² 100x +250 -12

10x² +100x +238